The impact of the interaction with beauty bloggers on follwers' purchase behavior - Fernandes, Catarina Andrea Pires (2016)
The rise of bloggers has been witnessed by the world during the last years. From fashion bloggers occupying the front row seats at haute couture défilés, to beauty bloggers partnering with the most prestigious cosmetics brands. The increasing relevance of these recently born celebrities in the markets they represent, and the every time more evident interest from brands, evidences bloggers’ work impact on what the players on the other side of the blogosphere benefit from: sales. In this sense, this study aims to identify possible consequences of the relation followers-blogger on beauty bloggers’ followers purchase behavior. Using an inductive reasoning and a methodology combining quantitative and qualitative approaches, the objective is to formulate possible theories from data observation. For the observation, data was collected through an online questionnaire with a sample of 67 beauty bloggers’ non followers and 80 beauty bloggers’ followers, and 5 in-depth interviews to cosmetics lovers and beauty bloggers’ followers. In both cases, respondents were only women. Results were analyzed with frequencies and means, to compare and find patterns. Beauty bloggers’ influence on followers’ purchase behavior is not questionable, though difficult to measure. They showed to be a pushed source of information that every cosmetics consumer has in consideration. The relationship with bloggers has shown to influence followers’ purchase intentions more than final decisions. Regarding purchase habits, the clearer pattern is the introduction of new brands and new products. The latter has shown bloggers marketing capacity to create needs. Finally, all the interaction follower-blogger increases followers’ interest on beauty products and thus the amount of products purchased per year boost, as does the total expenditure.